ANALYSIS OF STRATEGY DEVELOPMENT OF LAYING CHICKEN LIVESTOCK BUSINESS IN NGAWI DISTRICT - Priyambodo, Dimas; Setiyani, Rahmawati; Novitaningrum, Restie (LPPM Universitas Duta Bangsa Surakarta, 2023)
This study aims to determine the development strategy that can be carried out by laying hens in Ngawi Regency. The data collection technique uses the purposive sampling method, the calculation method uses the SWOT analysis quadrant and the SWOT matrix analysis method. The data used is primary data. Based on the results of the SWOT matrix analysis for Ngawi Regency, a strategy can be obtained that farmers can implement, namely the SO strategy: a) Increase the amount of production by increasing the population of laying hens, b) optimize egg production. WO strategy: a) Promoting livestock business, b) Keeping books of livestock business in order to control income and expenses. ST strategy: a) Establish good relations with collectors and consumers, b) Maintain product quality to face competitors, c) Determine the right strategy for selling chicken eggs, so that eggs can be sold every day. WT Strategy: a) Establish relationships with raw material suppliers, b) Maintain the cleanliness of the chicken coop. Based on the Quadrant SWOT analysis, Ngawi Regency is in quadrant I. Development strategies that can be implemented are a) Maintaining egg quality, b) Maintaining the quality of laying hen seeds, c) Increasing the laying hen population, d) Expanding marketing further.